An Empirical Study on Public Sector versus Third Sector Circular Economy-Oriented Innovations - Gary Walpole (Sustainability, 2024)
Extensive research has explored organisational dynamics across various sectors in relation to circular economy (CE) innovation practices. However, a critical gap exists in understanding CE innovation activities in the public sector versus the third sector. This distinction is crucial as the third sector’s role in CE innovation is growing, necessitating tailored policies instead of homogenous integration into public sector-based approaches. We address this gap by focusing on nuanced comparisons between the public and third sectors, delving into the motivations and constraints surrounding CE innovations across these different sectors. Employing an exploratory sequential design, we integrate qualitative insights from 12 interviews with quantitative measures derived from 153 survey responses within CE innovation communities. The findings reveal subtle yet significant disparities in innovation activities between the public and third sectors within a CE innovation community. Notably, cost factor differences related to the availability of finance and knowledge factors associated with the lack of information on technology emerge. This research contributes evidence-based insights, offering practitioners and policymakers a nuanced understanding of the motivations and constraints of circular economy innovation. These findings can be instrumental in steering the transition towards a more sustainable and circular economy, emphasising the need for tailored strategies rather than a one-size-fits-all approach.